Branding as risk management: Learning to love the consumer and lose control. Issue 10 (14th September 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Many people believe that the key to successful marketing is control. Control over brand, control over communications and control over activities. It is hard to imagine Apple opening up its hardware or software to customers so that they could create their own designs on its products, isn't it? Or General Motors for that matter. Or Pepsi. With pretty much any major brand you can think of, it is hard to imagine any of them ceding control. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.